Epidemiology of substance abuse in the population of Lucknow - Sumit Kumar; Divya Mehrotra; Shambhavi Mishra; M.M. Goel; Sandeep Kumar; Prashant Mathur; Kishore Choudhary; C.M. Pandey (Journal of Oral Biology and Craniofacial Research)
Background: Habit of consuming tobacco and areca-nut containing substances is in vogue in Lucknow as a part of the Nawabi culture. Hence, this study was planned with an aim to generate evidence for the prevalence of habits of substance abuse by the population of Lucknow and know their socio-demographic profile. Methodology: Population based cross-sectional study was conducted by organizing oral health check-up camps in randomly selected rural and urban parts of Lucknow, the capital city of Uttar Pradesh, which is the most populated state of India. Patients were enrolled after obtaining informed consent. A structured and validated questionnaire based tool was administered by a team of trained dental surgeons for collecting the desired information through interview and their oral cavity examination. Results: A total of 3437 subjects were enrolled in the study, out of which 82.9% were male and 17.1% were female. Among them, 64.6% subjects belonged to rural domiciliary status, by religion, 80.6% and 18.5% of the subjects were Hindu and Muslims respectively. The most prevalent habit was consumption of smokeless tobacco substances, of which pan masala with tobacco (gutkha) was the most prevalent substance of abuse. Conclusion: Smokeless tobacco consumption was highly prevalent in the population surveyed. It is recommended to formulate and implement strong preventive strategies. Also, steps should be taken to increase the awareness of the harmful consequences of these habits.